A new measurement method of actual focal spot position of an x-ray tube using a high-precision carbon-interspaced grid. (19th April 2018) - Lee, H W; Lim, H W; Jeon, D H; Park, C K; Cho, H S; Seo, C W; Lee, D Y; Kim, K S; Kim, G A; Park, S Y; Kang, S Y; Park, J E; et al.
Abstract: This study investigated the effectiveness of a new method for measuring the actual focal spot position of a diagnostic x-ray tube using a high-precision antiscatter grid and a digital x-ray detector in which grid magnification, which is directly related to the focal spot position, was determined from the Fourier spectrum of the acquired x-ray grid's image. A systematic experiment was performed to demonstrate the viability of the proposed measurement method. The hardware system used in the experiment consisted of an x-ray tube run at 50 kVp and 1 mA, a flat-panel detector with a pixel size of 49.5 µ m, and a high-precision carbon-interspaced grid with a strip density of 200 lines/inch. The results indicated that the focal spot of the x-ray tube (Jupiter 5000, Oxford Instruments) used in the experiment was located approximately 31.10 mm inside from the exit flange, well agreed with the nominal value of 31.05 mm, which demonstrates the viability of the proposed measurement method. Thus, the proposed method can be utilized for system's performance optimization in many x-ray imaging applications.